Metformin modulates the gut microbiome in a mice model of high-fat diet-induced glycolipid metabolism disorder. Issue 6 (13th December 2022) - Wu, Haoran; Wang, Xinmiao; Fang, Xinyi; Lian, Fengmei; Li, Min; Liao, Jiangquan; Dai, Dan; Tian, Jiaxing
Abstract : Introduction: Metformin (MET) can regulate glucose and lipid levels, and the gut microbiota may be involved in the control of metabolism. We hypothesized that MET alleviates glucolipid metabolism disorder by modulating gut microbiota and microbial metabolites. Research design and methods: A total of 24 male C57BL/6 J mice were equally divided into three groups (normal control, model control (MC), and MET-treated groups). Model mice were established by feeding a high-fat diet for 6 weeks. The MET-treated group was administered MET solution (2.5 g/100 mL, 250 mg/kg). Fecal samples were collected to characterize the microbiota system using metagenomic shotgun sequencing and gas chromatography–time of flight–mass spectrometry analysis. Phenotypic and biochemical indices were obtained for further correlation analysis. Results: Compared with the MC group, MET reduced the levels of weight, glucose, areas under the glucose curve in the glucose tolerance test, triglyceride (TG), and total cholesterol (TC). A decreasing abundance of bacteria, including Parabacteroides distasonis, and an increasing abundance of bacteria, including Bacteroides vulgatus, were observed in the MET-treated group. The 2-deoxytetronic acid declined after MET intervention and was positively correlated with species over-represented in the MC group and negatively correlated with species enriched in the MET-treated group. Additionally, species enriched in the MET-treated group negatively correlated with glucose, areas under the glucose curve in the glucose tolerance test, and TGs. Further, the correlation between the differential metabolites, which decreased after MET intervention, and the phenotypic indices was positive. Conclusions: MET-induced restoration of intestinal homeostasis correlates with the amelioration of host glucolipid metabolism.